2010
DOI: 10.1016/s0034-7094(10)70075-1
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Hemodynamic Assessment of Non-pregnant, Healthy Pregnant and Preeclamptic Women using Bio-Reactance

Abstract: The NICOM device is simple to use, operator independent, and provides clear and consistent monitoring signals. The output identified distinct hemodymamic profiles that are consistent with the findings of more invasive existing methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 25 publications
0
12
0
4
Order By: Relevance
“…Several studies have indicated that the LL position is the best position for a pregnant woman on a traditional stretcher 5,8,9,15,16,17. However, prior to this study, there were no references in the medical literature to the PP on stretchers specifically designed for pregnant women.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have indicated that the LL position is the best position for a pregnant woman on a traditional stretcher 5,8,9,15,16,17. However, prior to this study, there were no references in the medical literature to the PP on stretchers specifically designed for pregnant women.…”
Section: Discussionmentioning
confidence: 97%
“…Its accuracy has been tested against that of thermodilution in both animals and humans, 15 and it has been used in pregnant patients. [16][17][18] The NICOM has been found to have acceptable accuracy, and it correlates well with more established methods of CO monitoring. 14 Little has been studied regarding the use of NICOM in patients with grossly abnormal cardiovascular anatomy; however, the underlying physics of bioreactance technology is based on thoracic pulsatility, which takes into account the entire volume of blood in the thoracic cage irrespective of which side it occurs in the cardiac anatomy.…”
Section: Discussionmentioning
confidence: 73%
“…This has also been noted previously, disproving the usual assumption that low systemic vascular resistance persists throughout pregnancy to term 13 . In fact, our group has recently demonstrated with the same technology that healthy pregnant women at term have a very similar hemodynamic profile when compared to non-pregnant women 14 . This should have significant implications for teaching and understanding clinical practice in the near future.…”
Section: Discussionmentioning
confidence: 92%
“…Bioreactance technology is a newer form of non-invasive continuous cardiac output monitoring 10,14 , and has recently been used in the obstetric population for the first time 14 . It is based on an analysis of the relative phase shifts of oscillating currents that occur when the current traverses the thoracic cavity, as opposed to the traditional bioimpedance-based system which relies only on measured changes in signal amplitude.…”
Section: Discussionmentioning
confidence: 99%